Considering the effects of ambient particulate matter on the lung function of motorcycle taxi drivers in Bangkok, Thailand. (1st February 2018) - Arphorn, Sara; Ishimaru, Tomohiro; Hara, Kunio; Mahasandana, Suwisa
ABSTRACT: The motorcycle taxi drivers of Bangkok have been heavily exposed to high concentrations of PM10 (particulate matter with an aerodynamic diameter ≤10 μm), and the impact of this on their lungs has been neither documented nor studied. This study examines the association between exposure to PM10 and lung function decline among motorcycle taxi drivers. A cross-sectional study was conducted in Bangkok between two groups: a subject group of motorcycle taxi drivers and control group of enclosed vehicle taxi drivers. The findings of the Thailand Pollution Control Department were used to estimate the annual ambient PM10 concentration levels in the metropolis. Pulmonary functions of motorcycle taxi drivers and enclosed vehicle taxi drivers were measured and compared using the Mann-Whitney test. Multiple linear regression analysis was applied to estimate the effects of PM10 exposure on the lung function of motorcycle taxi drivers. A total of 1283 motorcycle taxi drivers and 600 taxi drivers were investigated. The mean forced expiratory volume in 1 sec/forced vital capacity (FEV1 /FVC) of the motorcycle taxi drivers was significantly lower than that of the taxi drivers ( P  < 0.001). The mean FEV1 /FVC of motorcycle taxi drivers exposed to ≥50 µg/m 3 PM10 was statistically lower (−2.82%; 95% confidence interval [CI]: −4.54% to −1.09%) and the mean % vital capacity (%VC) of those exposed to 40–49.9 µg/m 3 PM10 was statistically lower than that of motorcycle taxi drivers exposed to <30 µg/m 3 PM10 (−3.33%; 95% CI: −5.79% to −0.87%). Motorcycle taxi drivers were directly exposed to air pollution in their working environment. As a result, their lung function might decrease more than that of enclosed vehicle taxi drivers. With the possible exposure to ≥50 µg/m 3 PM10, the vehicular emission standards should be vigorously enforced. Further investigation is warranted to clarify the effect of lung dysfunction on the work and lifestyle of motorcycle taxi drivers. Implications : Motorcycle taxi drivers are directly exposed to air pollution in their work environment; therefore, their lung function might decrease more than that of enclosed vehicle taxi drivers, especially when exposed to ≥50 µg/m 3 PM10 . World Health Organization (WHO) vehicular emission standards should be recognized and eventually enforced.